The Depiction of Man in the Pull of the Times on Arsip Aku di Kedalaman Krisis By Afrizal Malna - Nur Alifah Septiani; Dedi Pramono; Bing CHI (Universitas Negeri Semarang, 2024)
Modern humans cannot be separated from digital technology. Interaction patterns in society attached to digital media give rise to various problems in human life in the real world. Its birth and death are uncertain in the digital world. Humans are presented with instability and helplessness. The digital world brings uncertainty to existence. This research aims to reveal human existence in the pseudo-digital world as depicted in the short story Arsip Aku di Kedalaman Krisis by Afrizal Malna. This type of research is qualitative descriptive with the perspective of literary works as social documents, explicitly looking at images of human existence. The results of this research show that (1) human images are always attractive in the real and virtual worlds, and (2) humans lose their definite identity in the world and become dependent on technology. Through this research, it is hoped that it can inform readers that a literary work in the form of a short story contains the values of human life. Literary works as social documents become criticism of the situation in the digital era. On the other hand, it indirectly reminds people that the digital world is risky if it only prioritizes technological sophistication without looking at the risks behind it.